2007
DOI: 10.1161/01.hyp.0000256361.68158.24
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mass, Blood Pressure, and Lowered Cognitive Performance in the Framingham Offspring

Abstract: Abstract-The purpose of this study was to determine whether echocardiographic left ventricular mass is related to cognitive performance beyond casual blood pressure adjusting for the influence of other vascular risk factors. We used multivariable regression analyses to relate left ventricular mass assessed at a routine examination (1995)(1996)(1997)(1998) to measures of cognitive ability obtained routinely (1998 -2001) A lthough there is an extensive literature on the association of blood pressure and cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 38 publications
7
42
1
2
Order By: Relevance
“…Our results are in agreement with previous studies that showed associations between cardiac damage and cognitive function 7, 8. However, as these studies did not investigate this association independently of brain damage, these results might be due to a high correlation between hypertensive cardiac damage and brain damage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in agreement with previous studies that showed associations between cardiac damage and cognitive function 7, 8. However, as these studies did not investigate this association independently of brain damage, these results might be due to a high correlation between hypertensive cardiac damage and brain damage.…”
Section: Discussionsupporting
confidence: 92%
“…These imaging markers of cSVD are strongly associated with cognitive function 3, 4, 5, 6. Other types of hypertensive organ damage, such as cardiac and renal damages, have also been linked to lower cognitive function or increased risk of cognitive impairment 7, 8, 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…Although this observation is consistent with some prior work,9, 10 the remaining null cognitive results contrast with literature reporting cognitive associations with LVH8 or increased LV mass index3, 28 in aging cohorts that include dementia cases. Although increased LV mass index is an early marker of pathologic LV remodeling, it may not strongly correspond with subtle cognitive changes in cognitively normal individuals or elders with only mild prodromal symptoms of dementia, such as those participants studied here.…”
Section: Discussionsupporting
confidence: 90%
“…Although increased LV mass index is an early marker of pathologic LV remodeling, it may not strongly correspond with subtle cognitive changes in cognitively normal individuals or elders with only mild prodromal symptoms of dementia, such as those participants studied here. Furthermore, prior work has shown that the association between increased LV mass index and cognition is attenuated when other cardiovascular risk factors are adjusted for,3, 8, 9, 10 as was done here with the inclusion of a vascular risk score.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation